Topping Out Ceremony for City Campus (Institutional Knowledge at Singapore Management University, 2004)
Singapore Management University Chairman Ho Kwon Ping addressing the audience at the topping out ceremony for SMU’s new city campus at Bras Basah. Picture taken on 18 October 2004.